Case Series of Guillain Barre Syndrome with Plasmaparesis in The ICU Bandung Hospital - Ridwan, Romi; Oktaliansyah, Ezra (CoinReads Media Prima, 2024)
Background: Guillain-Barré syndrome (GBS) is an autoimmune disease of the peripheral nervous system, which is clinically characterized by tetraplegia with or without sensory disturbances. Manifestations include weakness, progressive muscle areflexia and can cause weakness in the respiratory muscles. This causes sufferers to need mechanical ventilation assistance. ICU complications such as lung infections and sepsis occur if treatment is prolonged. Plasmaparesis in GBS is a therapy other than IVIG (IntraVenous ImmunoGlobulin) administration. Case report: We compared 2 cases, 42 years old (man A) and 31 years old (man B), with respiratory failure due to GBS were treated with plasmaparesis for 5 cycles. Patient A showed faster clinical improvement results. It took 6 days to get off mechanical ventilation on patient A, while on day 11 patient B still needed mechanical ventilation, with persistent tetraparesis. Conclusion: This case highlights the importance of using TCD and NIRS in the intensive care unit as guiding therapies in maintaining patient blood pressure, administering blood components, and early detection of complications such as cerebral vasospasm.